INFLUENCE OF LAND USE CHANGE ON THE DETAILED SPATIAL PLAN IN BANTUL REGENCY - Priyanto, Priyanto; Irwan Prasetyo; Harjono Padmono Putro (Sean Institute, 2021)
There are changes in area that have narrowed and some have experienced widening. The purpose of this study is to analyze land use changes that are not in accordance with the Detailed Spatial Planning (RDTR) of Kasihan District. Analyzing the problem of incompatibility of land use changes in Kasihan District with the Draft Regional Regulation on the RDTR of Kasihan District, as well as developing a handling strategy to overcome land use changes that are not in accordance with the RDTR of Kasihan District. The methodology used in this research is descriptive quantitative analysis, comparative analysis, GIS analysis and Analytic Hierarchy Process (AHP). The data collection technique is primary data and secondary data and uses purposive sampling. This study used a questionnaire to collect data from the community and experts in Kasihan District as respondents. Based on the results of the opinions of experts using the AHP analysis method, it is concluded that absorbing the aspirations of the community for the next RDTR planning by socializing the RDTR regulations to the community so that land use irregularities do not happen again.